Synthesis and Cytotoxic Studies of Hydroximino Derivatives of Some 16E-Arylidenosteroids - Chattopadhaya, Raja; Jhidal, Dharam Paul; Minu, Maninder; Gupta, Raiiju (Arzneimittelforschung, 2004)
Oxime and dioxime derivatives of various 16E-arylidenosteroids in the androstene series have been prepared and evaluated at the National Cancer Institute (NCI), Bethesda (USA) for their antineoplastic activity against various tumor cell lines in order to determine the structural requirements for cytotoxic activity. Aldol condensation of dehydroepiandrosterone (DHA) and DHA acetate with various aldehydes followed by treatment with hydroxylamine hydrochloride resulted in the formation of 16E-arylidenosteroid-oxime system. Oximes 15, 16 and compound 20 with a higher degree of oxidation in ring A have been found active in a 60 cell line antitumor prescreen by virtue of their cytotoxic effect against one or more tumor cell line and were further referred for in vivo hollow fiber bioassay. These compounds showed interesting intraperitoneal and subcutaneous scores in the in vivo hollow fiber bioassay and have been referred to the Biological Evaluation Committee for Cancer Drugs for further detailed in vivo testing.
Keywords: Antineoplastic agents; 16-Arylidenosteroids, antineoplastic activity, hydroxim-ino derivatives; oximes and dioximes, synthesis